Methodology for optimizing the headcount based on simulation modeling - Vladimir Ivanovich Gaiduk; Maria Vladimirovna Golovko; Eldar Yeristemovich Takaho (E3S Web of Conferences, 2024)
The article discusses the advantages of simulation modeling of the number of sales personnel in order to increase the economic efficiency of the organization. Headcount optimization aims to generate savings while meeting the organization’s goals. This example considers the activities of one of the leading players in the regional food market. In accordance with the general structure of the processes of receiving and servicing customers in the organization, their simulation model was developed in the GPSS World software environment. The obtained conclusions are economically substantiated.